IN VITRO SCREENING FOR ACETYLCHOLINESTERASE ENZYME INHIBITION POTENTIAL OF MUTHU PARPAM – THERAPEUTIC LEAD FOR ALZHEIMER’S DISEASE - N, SABARI GIRIJA; S, GUPTAJ; MA, SINEKHA; L, SAKTHIMANIPRIYA; P, SHANMUGAPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Siddha system is an ancient traditional system of medicine treats many chronic ailments and neurological disorders. Muthu parpam is one of the herbo marine Siddha drugs which have the indication for neurocognitive dysfunction. The main objective of this current study was to evaluate the acetylcholine esterase (AChE) inhibition of Muthu parpam. Methods: AChE activity was evaluated using a modified 96-well microplate assay based on Ellman’s method. Physostigmine (5, 10, 20, and 40 μg/ml) was used as the positive control. Results: The result of this study clearly indicates that the test drug Muthu Parpam was effective in inhibiting AChE enzyme at the specified concentration dose dependently. Maximum percentage inhibition of about 71.68% was observed at 500 μg/ml when compared to that of the Physostigmine, a known AChE inhibitor with the maximum inhibition 84.87% at the concentration of 40 μg/ml. Conclusion: Hence, this preliminary screening has proven the efficacy of Muthu parpam through AChE inhibition potential in the management of Alzheimer disease.